PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MODERASI - Setiawan, Didik; Suripto, Suripto; Rosini, Iin (Jurnal Riset Terapan Akuntansi, 2024)
This research aims to find out and analyze whether Corporate Social Responsibility, Intellectual Capital have an effect on company value. With Financial Performance as a Moderating variable. This type of research is associative quantitative research, using secondary data. The data analysis method used is a panel data regression test using Microsoft Excel and Eviews 12 applications. The population in this research is the Jakarta Islamic Index 70 companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Data collection techniques in research. The sampling technique was saturated with the results of 70 research populations becoming 46 companies with an observation period of 5 years, so that 230 data were processed in this research. The research results show that Corporate Social Responsibility influences company value, Intellectual Capital influences company value, Financial Performance Moderates the relationship between Corporate Social Responsibility and company value, Financial Performance Moderates the relationship between Intellectual Capital and company value. Keywords: Company Value, Corporate Social Responsibility, Intellectual Capital, Financial Performance